DETERMINAN NILAI PERUSAHAAN PADA PERUSAHAAN KONSTRUKSI YANG LISTING DI BEI PERIODE 2019-2022 - Fitri Anggaraeni, Annisa; Lusiana Yulianti, Maria; Janizar, Syapril (Departement of Civil Engineering, Universitas Winaya Mukti, 2024)
The aim of this research is to determine and analyze: The influence of capital structure and company growth on profitability and its implications for company value in a study of construction companies listed on the Stock Exchange for the 2019-2022 period, both simultaneously and partially. The research method used in this research is the nature of this data is time series data, namely from 2019 to 2022. The data used in this research are monthly index numbers from December 2019 to December 2022. The type of investigation is causality, and The time horizon in this study is cross-sectional. Based on the research results, it was found that capital structure has a positive and significant effect on profitability in construction Companies on the IDX in 2019-2022; company growth has a positive and significant effect on profitability in construction Companies on the IDX in 2019-2022; Capital structure has a positive and significant effect on company value in construction Companies on the IDX in 2019-2022; company growth has a positive and significant effect on company value in construction Companies on the IDX in 2019-2022; positive and significant influence on company value construction Companies on the IDX in 2019-2022. Capital Structure and Company Growth simultaneously influence profitability and its impact on company value in construction Companies listed on the IDX in 2019-2022. Keywords: Capital Structure, Company Growth, Profitability and Company Value